Active and engaging classrooms : a practical exploration of higher education - Schlein, Candace; Crump, Sara (Contemporary perspectives on curricular interactions, behavior, relationships, and classroom management, 2024)
"The notion of active and engaging learning is examined across diverse school levels and educational settings in this book. The overarching aim of this book is to expand discussion of active and engaging classrooms from multi-disciplinary and practical perspectives. The included chapters in this book represent a mix of classroom-based research from a variety of research methods and inquiry traditions. Chapters in this book also approach a literature review of this significant topic in curriculum and instruction. Moreover, this text offers a solid focus on disseminating the discussion of practical tips, tricks, and recommendations for practice regarding active teaching and high impact instructional practices. Many of the chapters offer authors' narratives of experiences that led to the development of specific practices, explanations of what worked and what did not work, and rationales for decisions. It is therefore anticipated that this work will support novice and experienced teachers with undertaking and/or enhancing their active and engaging teaching approaches and practices. We also invite teacher educators and student teachers to reference this book in support of teacher education and development in ways that are attuned to enhancing teaching and learning"-- Provided by publisher.